PENYULUHAN AKAN BAHAYA JUDI ONLINE PADA MASYARAKAT DESA RIDOGALIH - Abdilah, Muhamad Afif; Aprilina, Vita; Al-Ramadhan, Muhammad Fakhran (Universitas Islam 45 Bekasi, 2024)
Gambling through the internet is growing rapidly at the moment, where individuals are engaged in virtual gambling activities through online platforms such as websites or applications connected to the internet. This psychoeducation aims to increase understanding as an effort to prevent damaging behaviors resulting from online gambling, and is expected to prevent respondents who have not yet been touched by online gambling from trying to play online gambling. The method used in this counseling uses lectures related to the dangers of online gambling. The target in this psychoeducation activity is male adolescents and adults aged 18-40 years with a total of 31 respondents. The pre-test results related to the understanding of the dangers of online gambling mastered by male adolescents and adults in Ridogalih Village are still relatively low, as evidenced by the number of participants experiencing this reaching 27 participants with a percentage of 87%. However, after the psychoeducation followed by the distribution of post-tests, there were significant results regarding the understanding gained by male adolescents and adults in Ridogalih Village, as evidenced by the high results experienced by 17 student council members with a percentage of 57%. Thus, it can be concluded that the psychoeducation carried out has a significant impact on the understanding of the dangers of online gambling in male adolescents and adults.